2023
DOI: 10.3390/insects14100807
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Melanaphis sacchari Microbiota and Antibiotic Treatment Effect on Insects

Beatriz Xoconostle-Cázares,
José Abrahán Ramírez-Pool,
Leandro Alberto Núñez-Muñoz
et al.

Abstract: Insects are under constant selective pressure, which has resulted in adaptations to novel niches such as crops. This is the case of the pest Melanaphis sacchari, the sugarcane aphid, native to Africa and currently spreading worldwide. The aphid undergoes successful parthenogenesis, causing important damage to a variety of crops and leading to important economic losses for farmers. A natural M. sacchari population grown in sorghum was studied to identify its microbiome through the sequencing of its 16S rDNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This insect negatively affects sorghum and other important crops. Sugarcane aphids are economically important; they feed on plant sap, leading to reduced yields and, in some cases, total sorghum losses [2,3]. Pest management strategies proposed for M. sacchari include biological control, determination of optimal planting dates, elimination of alternative hosts, and the use of pesticides, with the latter being the primary control measure for this insect [4].…”
Section: Introductionmentioning
confidence: 99%
“…This insect negatively affects sorghum and other important crops. Sugarcane aphids are economically important; they feed on plant sap, leading to reduced yields and, in some cases, total sorghum losses [2,3]. Pest management strategies proposed for M. sacchari include biological control, determination of optimal planting dates, elimination of alternative hosts, and the use of pesticides, with the latter being the primary control measure for this insect [4].…”
Section: Introductionmentioning
confidence: 99%
“…SCA, like other insects, have a diverse microbial community as well as harbouring an obligate endosymbiont [5]. Recently, it was shown that antibiotic treatment of the SCA population resulted in a decreased survival rate [6], suggesting that SCA microbiota plays a crucial role in insect development.…”
Section: Introductionmentioning
confidence: 99%